(untitled) (Research, Society and Development, 2021)
Object: to evaluate the frequency of overweight in women with Polycystic Ovarian Syndrome (PCOS) and associations with cardiovascular risk. Methodology: a cross-sectional study with 44 women with a diagnosis of PCOS and age between 21 and 50 years. Anthropometric variables (Body Mass Index - BMI, Waist Circumference - CC, Waist-Hip Ratio - WHR and Waist-Stature Ratio - STt) were analyzed, sociodemographic variables (age, income, marital status, sedentary lifestyle, family history) and clinical variables presence of Melito Diabetes, Systemic Arterial Hypertension and / or Menstrual Irregularity). The statistical tests used for frequencies, associations and comparisons were: Chi-square, Fisher’s exact, F (ANOVA) and Kruskal-Wallis, with a significance level of 5%. Results: the majority of the group presented obesity (52.2%) followed by overweight (25%), high STCh (72.7%), high STC (65.9%) and high STCh (68.2%), ≤ 0.001; without associated chronic pathologies; (21-39 years), non-white, single women residing in the interior of the state, with menstrual irregularity and sedentary lifestyle predominated. Conclusion: overweight was present in almost all of the sample, with all the anthropometric indices showing a high cardiovascular risk, with the RCEst and CC being higher than the BMI and WHR in the risk classification.